Comparación de los usos del chuchuhuasi (Maytenus macrocarpa) entre indígenas Bora-Bora de Loreto y chamanes de Lima (Perú) - Salazar, Alberto (2013)
Abstract: Aim: To compare the knowledge and custom about the chuchuhuasi (Maytenus macrocarpa) uses between native ethnic Bora-Bora Amazon populations (Iquitos, Loreto) and the healers living in Lima, Peru. Methods: The study was performed through oral interviews to a number of native Bora-Bora and healers from Lima, who voluntarily agreed to participate. We collected information about knowledge and custom in the use of chuchuhuasi. Results: Although on a purely commercial context, the healers from Lima reported to use chuchuhuasi for the following purposes: to cure asthma, as analgesic, and for sexual problems; and also they used it for mystical, magical, and religious purposes during healing sessions. The Amazonian Bora-Bora indigenous use chuchuhuasi for medicinal purposes, particularly for severe pain, postpartum pain, to stop postpartum bleeding, and as antidiarrheal. Conclusions: There are differences in the use of chuchuhuasi between native Bora-Bora Amazonian population, and healers in Lima, Peru (AU)